Anti-oomycete Activity of Chlorhexidine Gluconate: Molecular Docking and in vitro Studies - Thakuria, Dimpal; Khangembam, Victoria C.; Pant, Vinita; Bhat, Raja Aadil Hussain; Tandel, Ritesh Shantilal; C., Siva; Pande, Amit; Pandey, Pramod Kumar (Frontiers in Veterinary Science, 2022)
Saprolegniosis is one of the most catastrophic oomycete diseases of freshwater fishes caused by the members of the genus Saprolegnia. The disease is responsible for huge economic losses in aquaculture industry worldwide. Until 2002, Saprolegnia infections were effectively controlled by using malachite green. However, the drug has been banned for use in aquaculture due to its harmful effect. Therefore, it has become important to find an alternate and safe anti-oomycete agent which is effective against Saprolegnia. In this study, we investigated the anti-oomycete activity of chlorhexidine gluconate (CHG) against Saprolegnia. Before in vitro evaluation, molecular docking was carried out to explore the binding of CHG with vital proteins of Saprolegnia such as S. parasitica host-targeting protein 1 (SpHtp1), plasma membrane ATPase and TKL protein kinase. In silico studies revealed that CHG binds with these proteins via hydrogen bonds and hydrophobic interactions. In in vitro study, the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of CHG against S. parasitica was found to be 50 mg/L. Further, it was tested against S. australis, another species of Saprolegnia and the MIC and MFC was found to be 100 mg/L and 200 mg/L respectively. At 500 mg/L of CHG there was complete inhibition on the radial growth of Saprolegnia hyphae. In propidium iodide (PI) uptake assay, CHG treated hyphae had bright red fluorescence of PI indicating the disruption of cell membrane. The results of the present study indicated that chlorhexidine gluconate could effectively inhibit Saprolegnia and hence can be used for controlling Saprolegniasis in cultured fish.